Ethical mindsets in the Australian services sector - Issa, Theodora; Pick, David (Springer, 2010)
The aim of this paper is to examine the existence of ethical mindsets in the Australian Services Sector and to investigate the role of spirituality and aesthetics in this phenomenon. Employing an interpretive mixed methods approach, data was collected via an online survey followed by focus groups interviews. The respondents to the online survey and the participants in the focus groups were from the Australian Services Sector. The results provide evidence of the existence of ethical mindsets and suggest that spirituality and aesthetics are major elements in those mindsets. Six components emerged from the analysis: aesthetic spirituality, religious spirituality, optimism, contentment, making a difference, and interconnectedness. While the results are limited to the Australian context, this research raises questions about the nature and role of ethical mindsets that are worthy of further research. These questions relate to the complexity and context dependency of ethical mindsets, and the role of intrinsic and extrinsic factors. In addition, these results demonstrat the usefulness of the interpretive mixed methods approach for analysing this complext issue.